(untitled) (Research, Society and Development, 2021)
The article evaluates the diffusion of the educational process for the qualification of SUS management in Oral Health in Paraná, conducted in four training cycles, from 2012 to 2019. It was used an exploratory study, of the ecological type. Maps were prepared using Course databases and QGIS Software for the Municipalities and Regional Health that adhered to and completed the four cycles, analyzing the diffusion of innovation through Rogers’ Diffusion of Innovation Theory. In total, 1,304 health professionals (multidisciplinary team) from 321 municipalities (80% of the municipalities of Paraná) volunteered to enroll, and 877 participants from 259 municipalities completed the course. This initiative presented relative advantage, compatibility, observability, experimentability and low complexity, besides using adequate communication channels and having the favor of the social system and the effort of agents of change in the process. It is concluded that the SUS Management Qualification Course in Oral Health presented the characteristics of the Innovation Diffusion Theory, setting up an innovative process in professional education with spread in the State of Paraná, reinforcing the role of the importance of teaching / service for the benefit of the population.